Pemanfaatan Media Pembelajaran Interaktif Berbasis Gamifikasi dengan Pendekatan Deep Learning bagi Guru SD - Silvi Puspa Widya Lubis; Riki Musriandi; Tamarli Tamarli; Miswar Miswar; Nila Syahfitri; Riska Muliana Lembong (Rengganis Jurnal Pengabdian Masyarakat, 2026)
Digital transformation in primary education requires teachers to adopt more innovative and adaptive learning methods. This Community Service (PKM) aims to enhance the competence of primary school teachers in utilizing interactive gamification-based learning media combined with a deep learning approach. The activity was conducted at SD Negeri Ulee Paya, Pulo Aceh District, involving teachers from the school. The implementation methods included surveys, counseling, face-to-face training, practice creating media using the Wordwall and Gimkid platforms, and an introduction to implementing simple deep learning to personalize learning materials. Evaluation was carried out through pre-tests and post-tests, observation of practice, and satisfaction questionnaires. The results showed an increase in participants' average knowledge, from 65 to 90, with 90% of teachers at Ulee Paya State Elementary School understanding the concept of gamification and the basic principles of deep learning. Teachers can create learning media using Wordwall and Gmkit applications. This activity increased motivation and understanding of technology among teachers at Ulee Paya State Elementary School, while also opening opportunities to apply adaptive learning at the elementary school level. Future recommendations include ongoing mentoring, the provision of computing infrastructure, and policy support to enable the widespread implementation of this innovation.